INTEGRASI ASUHAN KEBIDANAN BERBASIS BUKTI DALAM PENCEGAHAN PENYAKIT TIDAK MENULAR PADA PEREMPUAN: LITERATURE REVIEW - Catur Setyorini; Dwi Indah Wulandari Wulandari; Hepti Widia Ningsih; Atina Maya Fadhila (Jurnal Komunikasi Kesehatan, 2026)
Background: Non-communicable diseases (NCDs) are the leading cause of morbidity and mortality in women, including during preconception, pregnancy, childbirth, and postpartum. Midwives have a strategic role in promotive and preventive efforts through evidence-based midwifery care to reduce NCD risk factors. Objective: To analyze scientific evidence regarding the effectiveness of evidence-based midwifery care in preventing NCDs in women throughout the life cycle. Methods: This study used the Literature Review method referring to the PRISMA 2020 guidelines. Literature searches were conducted on PubMed, Scopus, ScienceDirect, SpringerLink, Wiley Online Library, and Google Scholar for articles published in 2020–2025. After the process of identification, screening, and eligibility assessment, 7 articles were obtained that met the inclusion criteria and were analyzed narratively. Results: The synthesis showed four main themes, namely the integration of NCD prevention in midwifery services, promotion of healthy lifestyles, implementation of Midwife-led Continuity of Care, and utilization of mobile health (mHealth). These interventions contribute to improved early detection of risk factors, changes in healthy lifestyles, increased adherence to antenatal care, and strengthened continuity of midwifery care. Conclusion: Evidence-based midwifery care plays a crucial role in preventing NCDs through a promotive, preventive, and continuous approach. Strengthening midwives' competencies and integrating NCD screening into midwifery services are necessary to improve the quality of women's health throughout the life cycle. Keywords: midwifery care, non-communicable diseases, evidence-based midwifery, continuity of care, systematic literature review.